The woman on the stairs - Schlink, Bernhard (Pantheon Books, 2017)
"A missing painting. A mysterious woman. Her husband and her lover. Here, the internationally acclaimed author delivers what his fans have been waiting for since The Reader--a powerful new novel about obsession, creativity, and love. A brilliant and naïve young lawyer's life is changed forever when a painter and his subject--a breathtakingly beautiful woman--appear at his office in Frankfurt. The woman's husband is deliberately marring the painting of his wife he commissioned the artist to make. Now the woman and the artist want the painting back. Simple enough--or so it seems before the lawyer becomes enmeshed in the lives of this toxic trio. Love, theft, and deceit unfold in quick succession when the woman, and the painting, suddenly go missing. It will take a strange turn of fate and a natural disaster to reunite the lawyer, the husband, and the artist with the woman they all love, hiding out in Australia--and when they find her they will be forced to reckon with the lies and betrayals of their shared past. This is an intricately crafted, poignant, and beguiling novel--it is Bernhard Schlink writing at his peak"--